The role of artificial intelligence in personnel management (Economics and region, 2025)
Currently, neural networks are widely distributed, greatly facilitating the work of specialists in many fields, but at the same time, they can create a number of problems that lead to fundamental changes in the process of human activity. Research shows that human adaptation to the widespread use of artificial intelligence is of paramount importance, as a result, it seems necessary to study this phenomenon using the IT field, since this field, on the one hand, is currently subject to automation, and on the other hand, it is highly dependent on the level of creative potential of employees. Since the application of artificial intelligence occurs in a large number of areas of human activity, including the IT field, an analysis of the principles underlying this process will help determine the most effective ways for people to adapt to automation. It is extremely important to study the spread of artificial intelligence from the position of combining philosophy (both analytical and cultural philosophy) and natural sciences, not independently of each other, because the separate study of automation, as it seems today, does not lead to the desired results and leads to increased uncertainty. The study of the socio-cultural context that has emerged in response to the application of artificial intelligence to various areas of life allows us to determine people's attitudes towards technological innovations and to identify the main features of various actions that have emerged in response to the development of artificial intelligence. It is also important to take into account modern approaches to the formation of ethical principles in the field of artificial intelligence. Currently, management based on artificial intelligence is gaining increasing popularity. In modern conditions, the management system of organizations, and in particular the HR sector, is under the inevitable influence of digital innovative transformation: business analytics, artificial intelligence and other advanced technologies. Taking all this into account, the article identifies the main features of artificial intelligence and the importance of applying artificial intelligence in personnel selection by organizations, and analyzes the advantages and potential risks of applying artificial intelligence technologies to the process of personnel management.
Keywords: artificial intelligence; personnel; management; technology; company; risk; coordination; control; automation